2006
DOI: 10.1080/01421590601105645
|View full text |Cite
|
Sign up to set email alerts
|

Student learning strategies, mental models and learning outcomes in problem-based and traditional curricula in medicine

Abstract: Kelson and Distlehorst (2000) state the PBL outcomes should be discussed on a broad basis including a useable knowledge base, skills in problem solving, self-directed learning and collaboration. The present research compares students in a PBL programme and in a traditional program on learning strategies, mental models and outcomes. Learning strategies and metal models of learning were measured for two student groups in 2001 using an adaptation of Vermunt's (1994) "Inventory of learning styles". Learning outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 14 publications
(18 reference statements)
2
53
2
6
Order By: Relevance
“…It would be particularly interesting to extend this research perspective, in order to understand how student learning can be influenced by educational innovations and interventions in longitudinal studies. An example is for instance the study of Lycke et al (2006), in which changes in students' regulation strategies and conceptions of learning have been examined across different educational programmes (traditional versus problem based). Another example is the study of Van der Veken et al (2009) in which changes in student learning were found between students endorsed in a conventional versus integrated contextual medical curriculum.…”
Section: Directions For Future Learning Patterns Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be particularly interesting to extend this research perspective, in order to understand how student learning can be influenced by educational innovations and interventions in longitudinal studies. An example is for instance the study of Lycke et al (2006), in which changes in students' regulation strategies and conceptions of learning have been examined across different educational programmes (traditional versus problem based). Another example is the study of Van der Veken et al (2009) in which changes in student learning were found between students endorsed in a conventional versus integrated contextual medical curriculum.…”
Section: Directions For Future Learning Patterns Researchmentioning
confidence: 99%
“…Recent research indeed showed evidence to support this claim. For example, Lycke et al (2006) compared medical students in a problem-based learning (PBL) programme and in a traditional programme on their use of learning strategies, conceptions of learning, and academic outcomes at a Norwegian Medical school. The results showed that PBL-students made more use of self-regulated learning strategies and had more constructive conceptions of learning than students in the traditional medical programme.…”
Section: Fostering the Quality Of Students' Learning Patternsmentioning
confidence: 99%
“…32,33 Several studies found that a person's preference for group learning contexts and the ability to self-regulate her learning strategies are positively related. 10,17,22 Possibly, students with good self-regulatory control perceive the complexity of group situations as positively challenging.…”
Section: Assessing Awareness Of Learning Strategiesmentioning
confidence: 99%
“…7 Beneficial teaching methods for these complex skills are small group work and self-regulated learning, case-based approaches, and constructivist learning environments, like problem-based learning (PBL). In these approaches knowledge and skills are acquired in interactive and co-constructive processes [9][10][11][12][13][14] that demand students' motivation to engage in group learning 15 , and their ability to self-regulate their learning activities. 16 However, beginning veterinary students were found to prefer individualistic learning over group work, and teacher-directed learning over self-directed studies.…”
Section: Introductionmentioning
confidence: 99%
“…The PBL allows learners to pursue information from any subject, and this allows them to deeply understand Physics concepts (Ates & Eryilmaz, 2011;Ball & Pelco, 2006;Cheong, 2008). Lycke, Grottum and Stromso (2006) demonstrated that PBL students showed "significantly more self-regulated learning and they perceived themselves as more active contributors to group learning process and used a broader range of resources than students in the traditional programme" (p. 113). Consequently, PBL environment can provide opportunities for students to develop their skills of self-directed learning which will help them to manage in designing, solve problems, performance, and evaluating learning outcomes (Bell, 2012;Downing, Ning, & Shin, 2011;Thornton, 2010;Whitcombe, 2013).…”
Section: Introductionmentioning
confidence: 99%